2017
DOI: 10.1038/srep43315
|View full text |Cite
|
Sign up to set email alerts
|

An inflammatory gene signature distinguishes neurofibroma Schwann cells and macrophages from cells in the normal peripheral nervous system

Abstract: Neurofibromas are benign peripheral nerve tumors driven by NF1 loss in Schwann cells (SCs). Macrophages are abundant in neurofibromas, and macrophage targeted interventions may have therapeutic potential in these tumors. We generated gene expression data from fluorescence-activated cell sorted (FACS) SCs and macrophages from wild-type and mutant nerve and neurofibroma to identify candidate pathways involved in SC-macrophage cross-talk. While in 1-month-old Nf1 mutant nerve neither SCs nor macrophages significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 59 publications
4
37
0
Order By: Relevance
“…CXCR3 ligand production is frequently associated with a myeloid cell response to IFN-γ signaling (46,47). IFN-γ is unlikely to drive Cxcl10 expression in neurofibroma; however, because Ifng expression is not detectable early in neurofibroma formation, in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG, IFN-γ levels in neurofibroma are low relative to other relevant cytokines (17). Rather, it appears that SCs, like CNS glia, produce Cxcl10 in an IFN-γ-independent fashion (47), because we found that Cxcl10 expression in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG localized to cell clusters expressing SC-associated genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR3 ligand production is frequently associated with a myeloid cell response to IFN-γ signaling (46,47). IFN-γ is unlikely to drive Cxcl10 expression in neurofibroma; however, because Ifng expression is not detectable early in neurofibroma formation, in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG, IFN-γ levels in neurofibroma are low relative to other relevant cytokines (17). Rather, it appears that SCs, like CNS glia, produce Cxcl10 in an IFN-γ-independent fashion (47), because we found that Cxcl10 expression in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG localized to cell clusters expressing SC-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, expression of Cxcl10 negatively correlated with expression of Ngfr and Gap43, markers that are associated with Remak SCs in vivo. In neurofibroma, when Ngfr-expressing SCs become axon dissociated, they secrete macrophage and mast cell chemokines (16,17,(50)(51)(52) but not Cxcl10. These data suggest that distinct SC subsets in neurofibromas produce different chemokines that contribute to tumor formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we evaluated other inflammatory signatures in these neurofibroma tumors. Macrophage is another type of inflammatory cell found in neurofibroma (40,41). Similar to mast cells, removed from the tumor microenvironment suggested that mast cells are a modifier rather than a driver in neurofibroma development ( Figure 2C).…”
Section: The Genotypes and Number Of Mice Enrolled In The Plexiformmentioning
confidence: 93%
“…Others using genomic approaches to explore nerve sheath tumor biology identified MET and HGF amplification in MPNSTs; furthermore, models of MET amplified MPNSTs were subsequently sensitive to the MET inhibitor capmatinib [7] . Transcriptomics-focused approaches have also identified molecular features like MEK signaling, type 1 interferon signaling, and Aurora kinase A as putative therapeutic targets in NF1 tumors [12][13][14] . Taken together, these and other studies suggest that an integrative approach that combines multiple transcriptomic and genomic datasets might be well poised to identify new therapeutic avenues in MPNSTs and other NF1 related nerve sheath tumors.…”
Section: Introductionmentioning
confidence: 99%